New Zealand's experiment with prudential regulation : can disclosure discipline moderate excessive risk taking in New Zealand deposit taking institutions? : a thesis presented in partial fulfillment of the requirements for the degree Doctor of Philosophy at Massey University, Albany - Wilson, William Robert (Massey University, 2009)
The New Zealand economy in the period up to 2006 provides an opportunity to assess an alternative disclosure based approach to the prudential regulation of deposittakers, in a market free of many of the distortions which arise from traditional regulatory schemes. The overall objective of this research has been to assess the effectiveness of the prudential regulation of New Zealand financial institutions and judge if the country is well served by it. Analysis of New Zealand’s registered bank sector suggests public disclosure adds value to New Zealand’s financial system. However, the significant relationship found between disclosure risk indicators and bank risk premiums was not as a result of market discipline, rather it is argued self-discipline was the mechanism, demonstrating bank management and directors are discharging their duties in a prudent manner. A feature of the New Zealand disclosure regime for banks is the significant responsibilities placed on bank directors; directors are then held accountable for their actions. Findings in the management of banks were in contrast to non-bank deposittakers, where disclosure was judged to be ineffective, and of no practical use due to its poor quality. The management of non-bank deposit-takers appeared to receive very little oversight from depositors, their trustees or official agencies. As a result, many appear to have managed their institution in their own interests, with little consideration given to other stakeholders. Failures which occurred in NBDTs from 2006 resulted from deficiencies in the prudential regulation of these deposit-takers, demonstrating the severity of asymmetric information and moral hazard problems which can arise if prudential regulation is not correctly designed and management interests are not aligned with other stakeholders. The New Zealand disclosure regime will never guarantee a bank will not fail, nor should it try to do so, but it should assist the functioning of a sound and efficient financial system. To this end, it is recommended that the Reserve Bank, in re-designing the regulatory framework for NBDTs, hold the management and directors of NBDTs similarly accountable, while also incorporating regular disclosure and minimum prudential standards. Governments have an important role to play in ensuring the financial system is efficient.
Keywords: Banks; Prudential regulation; Disclosure (Accounting); Risk-taking; New Zealand; Banking state supervision; Fields of Research::350000 Commerce, Management, Tourism and Services::350300 Banking, Finance and Investment